Vibration suppression of rotating disc using eddy current method - Mohd Izuan, Hashim (2013)
This paper presents about the vibration behaviour on rotating aluminum disc using eddy current method. By increasing the induce current with different initial speed and different air-gap it make a different vibration behavior. The changing magnetic ﬂux induces eddy currents in the conductor. These currents dissipate energy in the conductor and generate drag force. One such method is eddy current damping. Magnetic damping scheme functions through the eddy currents that are generated in a nonmagnetic conductive material when it is subjected to a time changing magnetic field. The result of this study show that the increasing of induce current, initial speed and air-gap give a significant effect to vibration behaviour effected from magnetic flux density and damping force.